SIDITA: SISTEM INFORMASI DINAS PERTANIAN TERINTEGRASI BERBASIS WEB - Beda Puspita Candra; Imam Thoib; Muhamad Sabil Shah Putra; Andoko Saifudin; Mochamad Dwi Andika; Fadhila Mu’afiyah; Ahmad Yusron Kafabi (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
Agricultural data management in Nganjuk Regency has traditionally been conducted manually using physical records and separate spreadsheets, leading to inefficiencies, data duplication, and delays in reporting. To address these challenges, this study developed SIDITA, a web-based integrated agricultural information system designed to centralize and streamline data management across multiple sectors including crops, livestock, farmer institutions, and agricultural aid distribution. The objective of this research was to provide a practical solution that enhances efficiency, accuracy, and accessibility of agricultural data for the local government. The system was developed using the CodeIgniter framework, MySQL database, and responsive interfaces with Bootstrap and Tailwind CSS, following the waterfall development methodology. Testing was conducted using black box methods to ensure functional reliability. The results demonstrate that SIDITA successfully integrates diverse agricultural data into a single platform, reduces redundancy, and improves the speed and accuracy of reporting. In conclusion, the implementation of SIDITA supports better decision-making processes in agricultural management and provides a scalable model for digital transformation in local government institutions.